Sistem Informasi Manajemen Penjualan Obat Pada Apotek Berbasis Web Dengan Menggunakan Metode Incremental Model - Badri, Fawaidul; Sari, Sulistya Umie Ruhmana (Jurnal Sistem Informasi Dan Informatika, 2023)
In the pharmacy system, there is a lot of drug data, transaction data, and others that are impossible to memorize. It takes a system that can record the data by making improvements in the management of a data processing system. Improvements that will be made are creating a recording system using a computer-based system, both in terms of inventory data collection, transaction data recording, and other processes related to activities at the pharmacy concerned. In designing this drug sales system using the waterfall method (SDLC) to find out the design for making the system needed. The purpose of this study is to find out the use of information systems based on drug sales, sales management and inventory of drug supply. The test results of this drug sales information system are proven by questionnaire respondents with almost 90% results, the use of this information system proves that it is very necessary and useful for the general public.